Association of sodium and potassium intake, nutritional status, and physical activity with blood pressure in diabetes mellitus patients in Pesanggrahan District Health Center - Ade Dwi Pangestu (ARGIPA (Arsip Gizi dan Pangan), 2019)
Diabetic patients have a 1,5 to 3 times higher risk of developing hypertension compared to non-diabetics. The proportion of hypertension in Indonesia in patients with DM is 51.8%. This study aims to determine the relationship between sodium and potassium intake, nutritional status, and physical activity with the incidence of blood pressure in DM patients in Pesanggrahan District Health Center. The study design used was cross-sectional, with a sample of 99 patients obtained from the purposive sampling method. The results showed that the average patient was 57 years old, female, and had been suffering from diabetes for five years. The average sodium and potassium intake are 2401 mg and 1460 mg respectively. The proportion of diabetic patients at the Pesanggrahan District Health Center who had high blood pressure was 83,8% and 78,8% of patients have central obesity, while 75,8% fall into the category of low physical activity. Based on the chi-square test, there is a significant relationship (p=0,000) between sodium intake, nutritional status, and physical activity with systolic blood pressure. There was a significant relationship between sodium intake, nutritional status, and physical activity with diastolic blood pressure (p= 0,000, 0,023, and 0,000). Keywords: blood pressure, diabetes mellitus, nutrient intake, nutritional status, physical activity